Hermeneutical Elements of Imam Ahmad bin Muhammad Al-Shawi in Tafsir Al-Shawi - Ilham Samuty; Mustapa Mustapa; Nurdiani Nurdiani (Fakultas Agama Islam, 2026)
This study examines the hermeneutical elements employed by Imam Ahmad bin Muhammad Ash-Shawi in interpreting Surah Al-Fatihah in Tafsir Ash-Shawi. The research is motivated by the importance of understanding the interpretive methodology of classical Muslim exegetes, which extends beyond literal textual analysis to encompass linguistic, contextual, historical, and spiritual dimensions. The study aims to identify and analyze the hermeneutical elements underlying Ash-Shawi's interpretation of Surah Al-Fatihah. A qualitative approach with a library research design was adopted. The primary data source was Tafsir Ash-Shawi, while secondary data were obtained from classical and contemporary works on Qur'anic exegesis, hermeneutics, and related scholarly literature. The findings reveal that Ash-Shawi's exegetical method integrates several hermeneutical elements, including linguistic analysis, transmitted traditions (tafsīr bi al-ma'thūr), rational argumentation, contextual interpretation, and isyārī (spiritual) as well as Sufi perspectives. These elements are harmoniously synthesized to produce a comprehensive interpretation while remaining grounded in the authority of the Qur'an, the Sunnah, and the opinions of classical scholars. The study concludes that Ash-Shawi's hermeneutical framework is integrative, combining textual, contextual, and spiritual approaches in interpreting Surah Al-Fatihah, thereby demonstrating its enduring relevance for the advancement of contemporary Qur'anic exegesis and hermeneutical studies.